A Scanning Electron Micrograph-based Resource for Identification of Loci Involved in Epidermal Development in Tomato: Elucidation of a New Function for the Mixta-like Transcription Factor in Leaves. Issue 5 (13th March 2020) - Galdon-Armero, Javier; Arce-Rodriguez, Lisette; Downie, Matthew; Li, Jie; Martin, Cathie
Abstract : A detailed screen of the Solanum lycopersicum cv M82 × Solanum pennellii ac. LA716 introgression line (IL) population revealed ILs with altered leaf trichome densities, abnormal proportions of different trichome types, and aberrant trichome morphologies leading to the identification of previously unexplored genomic regions with roles in trichome formation in tomato. Abstract: The aerial epidermis of plants plays a major role in environmental interactions, yet the development of the cellular components of the aerial epidermis—trichomes, stomata, and pavement cells—is still not fully understood. We have performed a detailed screen of the leaf epidermis in two generations of the well-established Solanum lycopersicum cv M82 × Solanum pennellii ac. LA716 introgression line (IL) population using a combination of scanning electron microscopy (SEM) techniques. Quantification of trichome and stomatal densities in the ILs revealed four genomic regions with a consistently low trichome density. This study also found ILs with abnormal proportions of different trichome types and aberrant trichome morphologies. This work has led to the identification of new, unexplored genomic regions with roles in trichome formation in tomato. This study investigated one interval in IL2-6 in more detail and identified a new function for the transcription factor SlMixta - like in determining trichome patterning in leaves. This illustrates how these SEM images, publicly available to the research community, provide an important dataset for further studies on epidermal development in tomato and other species of the Solanaceae family.